2012
DOI: 10.1016/j.acvd.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The role of echocardiography in the assessment of right ventricular systolic function in patients with transposition of the great arteries and atrial redirection

Abstract: Owing to geometric changes, presumed contractility pattern shift and retrosternal position, conventional echocardiographic variables are not relevant for RV function assessment. Assessment of asynchrony and tricuspid regurgitation is easily feasible in routine practice and highly reproducible. Echocardiography does not permit complete assessment of the systemic RV after atrial redirection but is fully complementary with MRI and should not be abandoned. Future improvements in transducers and dedicated software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…studied 24 patients, and found a fair correlation between TAPSE and first‐pass radionuclide RVEF . Iriart and coworkers found no correlation between TAPSE and MRI‐RVEF in the 35 patients they studied, comparing a multivariable transthoracic echocardiographic analysis with MRI . But in the 18 patients studied by Lissin et al.…”
Section: Discussionmentioning
confidence: 96%
“…studied 24 patients, and found a fair correlation between TAPSE and first‐pass radionuclide RVEF . Iriart and coworkers found no correlation between TAPSE and MRI‐RVEF in the 35 patients they studied, comparing a multivariable transthoracic echocardiographic analysis with MRI . But in the 18 patients studied by Lissin et al.…”
Section: Discussionmentioning
confidence: 96%
“…Studies of HLHS patients at other stages of palliation support the notion that the systemic RV adopts a circumferential contraction pattern, similar to the systemic left ventricle [11, 22]. Similarly, patients with d-transposition of the great arteries and systemic RVs after atrial redirection procedures (Mustard/Senning operations) also demonstrate a predominance of circumferential strain over longitudinal strain on speckle-tracking echocardiography of the RV [1, 7, 8, 23]. Values of TAPSE are diminished in this population as well and correlate poorly with RVEF [4, 8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, decreased TAPSE in patients with systemic RVs after atrial redirection procedures for transposition of the great arteries has been described [7, 8]. However there are limited reports of TAPSE in patients with single, systemic RVs [9, 21], for whom a refined, noninvasive assessment of RV function on transthoracic echocardiogram (TTE) is of fundamental importance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex geometry of the RV, quantitative 2D and Doppler measures by echocardiography are difficult to perform, correlate modestly at best with CMR estimates of ejection fraction and are not routinely used in clinical practice(79). Prior analysis of this SVR cohort has shown that standard echocardiographic measures of RV systolic and diastolic function are similar between shunt groups at 14 months(10).…”
Section: Introductionmentioning
confidence: 99%